Enhanced salivary secretion by interferential current stimulation in patients with dry mouth: a pilot study - Hasegawa, Yoko; Sugahara, Kazuma; Sano, Saori; Sakuramoto, Ayumi; Kishimoto, Hiromitsu; Oku, Yoshitaka (Oral surgery, oral medicine, oral pathology and oral radiology, 2016)
This pilot study tested the effects of submandibular and sublingual gland stimulation by interferential current stimulation (IFCS), a noninvasive mode of electrical stimulation. Three groups were enrolled in this study: 20 young adults, 19 older adults, and 21 patients with dry mouth. Four electrodes were attached to the submandibular area, and the secreted saliva was collected by using Salivette cotton rolls (Sarstedt K. K., Tokyo, Japan) for 15 minutes, either with or without IFCS. Patients were randomly chosen to receive IFCS. Each subject rated pain and discomfort on the Visual Analogue Scale (VAS) after each experiment. Saliva chromogranin A levels were measured as a stress marker. To compare data between conditions with and without IFCS, a two-sample Student t test analysis was performed. Saliva flow was slightly increased in those in the dry mouth group receiving IFCS compared with those who did not receive IFCS (approximately 130%). However, no such difference was found in the young and older adult groups. There was no significant difference in the VAS values of pain and discomfort or in the stress marker levels between patients who received or did not receive IFCS in the three groups. IFCS delivered to submandibular and sublingual glands may promote saliva secretion in persons who suffer from dry mouth in a manner that does not induce pain or physical stress.